Internalization of Pancasila Values Through School Cultivation During the Covid-19 Pandemic - Harnanto Harnanto (Universitas of Muhammadiyah Makassar, 2022)
Internalization of Pancasila values must be given to students. Teachers need to find creative, innovative, inspirational, and contextual ways to cultivate Pancasila values in schools. This study aims to describe the results of best practices that have been carried out by teachers in cultivating Pancasila values during the Covid-19 pandemic. This research is a descriptive qualitative research. Data was collected by means of document studies, literature studies, observations, interviews, and documentation. The research sites are Al Falah Darussalam Elementary School, Sidoarjo Regency, East Java Province and 4 Bucu State Elementary School, Jepara Regency, Central Java Province. The results of the study indicate that the media created by the teacher in cultivating the values of Pancasila for students is very creative and innovative. Garuda BMT and Bupanca media can increase the internalization of Pancasila values and students' creativity. Collaboration between teachers and parents is very important for the successful internalization of Pancasila values during independent learning at home. The cultivation of Pancasila values is something important that must be done by teachers continuously in line with the dynamics of the life process of the nation and state. Internalisasi nilai-nilai Pancasila harus diberikan kepada peserta didik. Guru perlu mencari cara kreatif, inovatif, inspiratif, dan kontekstual dalam pembudayaan nilai-nilai Pancasila di sekolah. Penelitian ini bertujuan untuk mendeskripsikan hasil praktik terbaik yang telah dilakukan oleh guru dalam pembudayaan nilai-nilai Pancasila dimasa pandemi Covid-19. Penelitian ini merupakan penelitian kualitatif deskriptif. Pengumpulan data dilakukan dengan cara studi dokumen, studi pustaka, observasi, wawancara, dan dokumentasi. Tempat penelitian di Sekolah Dasar Al Falah Darussalam, Kabupaten Sidoarjo, Provinsi Jawa Timur dan Sekolah Dasar Negeri 4 Bucu, Kabupaten Jepara, Provinsi Jawa Tengah. Hasil penelitian menunjukkan bahwa media yang dibuat oleh guru dalam pembudayaan nilai-nilai Pancasila terhadap peserta didik sangat kreatif dan inovatif. Media Garuda BMT dan Bupanca dapat meningkatkan internalisasi nilai-nilai Pancasila dan kreativitas peserta didik. Kolaborasi guru dengan orang tua sangat penting dilakukan untuk keberhasilan internalisasi nilai-nilai Pancasila pada saat pembelajaran secara mandiri di rumah. Pembudayaan nilai-nilai Pancasila merupakan sesuatu yang penting harus dilakukan oleh guru secara terus menerus sejalan dengan dinamika proses kehidupan berbangsa dan bernegara.